Check-list of Bromeliaceae from Mato Grosso do Sul, Brazil - de Melo Versieux, Leonardo; Coffani-Nunes, João Vicente; Matos Paggi, Gecele; Ferreira da Costa, Andrea (Iheringia, Série Botânica., 2018)
A checklist of 11 genera and 41 species of Bromeliaceae occurring in the state of Mato Grosso do Sul (MS) is presented. Of the total number of species, five are endemic and belong to the genera Dyckia and Tillandsia. The subfamily Pitcairnioideae is the richest in number of genera and species, including taxa that are rare in Brazil (Deuterocohnia and Fosterella). Tillandsioideae is the richest subfamily in species number plus one infraspecific taxon; however, it is only represented by Tillandsia, and most species are widely distributed all over Brazil and/or nearby countries. Bromelioideae, a subfamily characteristic of the Atlantic rainforest is less represented. This checklist updates the number of species in Mato Grosso do Sul, when compared to the Official Brazilian Plant Checklist.